Phosphatidylethanolamine Is Not Essential for Growth of Sinorhizobium meliloti on Complex Culture Media - Sohlenkamp, Christian (American Society for Microbiology, 2004)
In addition to phosphatidylglycerol (PG), cardiolipin (CL), and phosphatidylethanolamine (PE), Sinorhizobium meliloti also possesses phosphatidylcholine (PC) as a major membrane lipid. The biosynthesis of PC in S. meliloti can occur via two different routes, either via the phospholipid N-methylation pathway, in which PE is methylated three times in order to obtain PC, or via the phosphatidylcholine synthase (Pcs) pathway, in which choline is condensed with CDP-diacylglycerol to obtain PC directly. Therefore, for S. meliloti, PC biosynthesis can occur via PE as an intermediate or via a pathway that is independent of PE, offering the opportunity to uncouple PC biosynthesis from PE biosynthesis. In this study, we investigated the first step of PE biosynthesis in S. meliloti catalyzed by phosphatidylserine synthase (PssA). A sinorhizobial mutant lacking PE was complemented with an S. meliloti gene bank, and the complementing DNA was sequenced. The gene coding for the sinorhizobial phosphatidylserine synthase was identified, and it belongs to the type II phosphatidylserine synthases. Inactivation of the sinorhizobial pssA gene leads to the inability to form PE, and such a mutant shows a greater requirement for bivalent cations than the wild type. A sinorhizobial PssA-deficient mutant possesses only PG, CL, and PC as major membrane lipids after growth on complex medium, but it grows nearly as well as the wild type under such conditions. On minimal medium, however, the PE-deficient mutant shows a drastic growth phenotype that can only partly be rescued by choline supplementation. Therefore, although choline permits Pcs-dependent PC formation in the mutant, it does not restore wild-type-like growth in minimal medium, suggesting that it is not only the lack of PC that leads to this drastic growth phenotype.